Sedimentation rate-based screening of oleaginous microalgae for utilization as a direct combustion fuel. (December 2019) - Sung, Young Joon; Patel, Anil Kumar; Yu, Byung Sun; Choi, Hong Il; Kim, Jongrae; Jin, EonSeon; Sim, Sang Jun
Graphical abstract: Highlights: Different cell sedimentation rate is effective for screening of oleaginous cells. Mutant strains having low sedimentation rate shows high lipid content. The isolated mutant strain had a 57.3% enhancement in lipid content. High lipid content of isolated mutant strain contributes to high LHV of biomass. Abstract: The co-combustion of microalgae biomass with coal has the potential to significantly reduce CO2 emissions by eliminating expensive and carbon-emitting downstream processes. In this study, the utilization of microalgal biomass as a direct combustion fuel in co-firing industries and the screening of potential oleaginous strains of high calorific value was investigated. High-lipid accumulating mutants were selected from mutant mixtures based on cell density using differential sedimentation rates. Of the mutant strains obtained in the top phase of the separation medium, 72% showed a higher lipid content than the wild-type strain. One mutant strain exhibited a 57.3% enhanced lipid content and a 9.3% lower heating value (LHV), both indicators of direct combustion fuel performance, compared to the wild-type strain. Our findings indicate that sedimentation rate-based strain selection allows for the easy and rapid screening of high-lipid content algal strains for the use of microalgae as direct combustion fuels.